The disagreement we overlook: Examining core and acquaintance networks in a presidential primary - Lauren Ratliff Santoro; Anand E. Sokhey (Research & Politics)
Research on interpersonal political discussion has focused on cross-party interactions. But how much disagreement exists between co-partisans in core networks, and what kinds of differences do we see in the broader acquaintance networks of co-partisans supporting different primary candidates? We use data from a nation-wide survey administered early in the 2020 Democratic nomination contest to examine these questions. In presenting descriptive analyses, we uncover substantial disagreement between Democrats—disagreement that would be missed entirely by traditional measures focused solely on whether individuals share partisanship or general election vote choice. We also find intriguing patterns when looking at the acquaintance networks of Democrats who supported different primary candidates. We discuss how studying intraparty disagreement can not only aid our understanding of how primary nomination contests mobilize distinct constituencies, but also suggest strategies for potentially mitigating interparty disagreement.